2018
DOI: 10.1111/desc.12768
|View full text |Cite
|
Sign up to set email alerts
|

Altered lateralization of dorsal language tracts in 6‐week‐old infants at risk for autism

Abstract: Altered structural connectivity has been identified as a possible biomarker of autism spectrum disorder (ASD) risk in the developing brain. Core features of ASD include impaired social communication and early language delay. Thus, examining white matter tracts associated with language may lend further insight into early signs of ASD risk and the mechanisms that underlie language impairments associated with the disorder. Evidence of altered structural connectivity has previously been detected in 6-month-old inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 91 publications
(132 reference statements)
4
26
0
Order By: Relevance
“…As language function is dependent on the structural integrity of language networks, it is expected that infants who later develop ASD and language delay should exhibit aberrant trajectories in both structural and functional connectivity of language networks during the first year of life. A recent neuroimaging study of a subset of infants from our cohort has documented altered structural lateralization of language networks in FR infants at 6‐weeks of age (Liu et al., 2019).…”
Section: Discussionmentioning
confidence: 83%
“…As language function is dependent on the structural integrity of language networks, it is expected that infants who later develop ASD and language delay should exhibit aberrant trajectories in both structural and functional connectivity of language networks during the first year of life. A recent neuroimaging study of a subset of infants from our cohort has documented altered structural lateralization of language networks in FR infants at 6‐weeks of age (Liu et al., 2019).…”
Section: Discussionmentioning
confidence: 83%
“…In addition, anatomical connections between frontal and temporal language regions subserve language production and syntactic processing ( Friederici, 2009 , 2011 ). These white matter tracts, which are critical for language development, are present in early infancy ( Liu et al, 2018 ; Perani et al, 2011 ) and are altered in HR infants as early as 1.5 months of age ( Liu et al, 2018 ). Our findings highlight that functional connectivity of these regions is also disrupted in HR infants.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we focused on examining connectivity between regions canonically associated with language processing and sensorimotor integration. Structural factors such as cortical surface area ( Hazlett et al, 2017 ), subcortical volume ( Swanson et al, 2017 ), and white matter development ( Liu et al, 2018 ; Wolff et al, 2012 , 2017a , 2017b ) are also altered in HR infants and may influence functional connectivity of these networks. Future research should thus aim to integrate structural metrics with measures of functional connectivity in the developing brain in at-risk populations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also found alterations in the SLF among individuals with ASD (Fitzgerald et al, 2018; Poustka et al, 2012; Weinstein et al, 2011). Moreover, a recent study showed that 6‐week‐old infants at risk for autism showed higher fractional anisotropy in the right SLF compared to low risk infants (Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%